Notes from the GLAD (Global sustainable Livestock Advocacy for Development) Network Meeting, 28 July 2022 - International Livestock Research Institute (International Livestock Research Institute, 2022)
A recording of the Global Livestock Advocacy for Development (GLAD) project network meeting held 28 July 2022 is here: https://youtu.be/W6vn140GmPs